Development of cultural spatial concepts for the preservation of local culture and the environment in the ecotourism area of Tamansari Village - Febriani, Yusi; Firmansyah, Yudi (Indonesian Journal of Applied Environmental Studies, 2024)
Areas designated as strategic tourism areas are those where tourism serves as the primary industry or has the potential to do so, as well as has a significant impact on one or more factors, such as the development of the economy, society, and culture, as well as the preservation of natural resources, the ability of the environment to support human habitation, and defense and security, through putting into practice the idea of ecotourism development, which is responsible tourism to natural areas that promote environmental preservation and enhances the well-being of locals. With a focus on local wisdom and a microcosm of Sundanese culture connected to Tamansari Village, the concept plan for developing the village's tourism areas combines ecotourism and local wisdom. ABSTRAK Kawasan yang ditetapkan sebagai kawasan pariwisata strategis adalah kawasan yang pariwisatanya berfungsi sebagai industri utama atau mempunyai potensi untuk itu, serta mempunyai dampak penting terhadap satu atau lebih faktor, seperti perkembangan ekonomi, masyarakat, dan budaya, serta serta pelestarian sumber daya alam, kemampuan lingkungan hidup untuk mendukung tempat tinggal manusia, serta pertahanan dan keamanan, melalui penerapan gagasan pengembangan ekowisata, yaitu pariwisata yang bertanggung jawab terhadap kawasan alam yang memajukan pelestarian lingkungan dan meningkatkan kesejahteraan. penduduk setempat. Dengan fokus pada kearifan lokal dan mikrokosmos budaya Sunda yang terhubung dengan Desa Tamansari, konsep rencana pengembangan kawasan wisata desa ini memadukan ekowisata dan kearifan lokal.